ANTIOXIDANT ACTIVITY AND SELECTED METABOLIC EFFECTS OF ETHANOL EXTRACT FROM MANGOSTEEN (Garcinia mangostana L.) PERICARP IN HIGH-FAT DIET–INDUCED MICE: AN IN VITRO AND IN VIVO STUDY - Thi Hien, Nguyen; Thi Tuoi, Le; Thu Ngan, Tran; Thi Hong Hanh, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2026)
Mangosteen (Garcinia mangostana L.) pericarp is a rich source of polyphenolic xanthones and other bioactive compounds with potential antioxidant and metabolic regulatory properties. This study investigated the in vitro antioxidant activity and selected in vivo metabolic effects of ethanol extract from mangosteen pericarp. Mangosteen pericarp collected from Lam Dong province was extracted with 60% ethanol. The extract was characterized for total phenolic content by the Folin–Ciocalteu method. Antioxidant capacity was evaluated using the DPPH radical scavenging assay. For the in vivo study, male white mice (Mus musculus) were divided into four groups: a regular diet (RD), a high-fat diet (HFD), a HFD with extract at 300 mg/kg, and a HFD with extract at 400 mg/kg. Liver weight, spleen weight, and fasting blood glucose levels were measured after 8 weeks. The extract exhibited a high total phenolic content (200.16 ± 17.71 mg gallic acid equivalents/g extract) and showed dose-dependent DPPH radical scavenging activity with a half maximal inhibitory concentration (IC50) value of 118.87 ± 13.56 μg/mL, indicating a moderate but reproducible antioxidant capacity. In vivo, the HFD group showed significantly increased blood glucose levels (10.38 ± 3.54 mmol/L) compared to RD controls (7.57 ± 3.45 mmol/L). Treatment with the extract at 400 mg/kg significantly reduced glucose levels (5.16 ± 0.93 mmol/L, p < 0.05) compared to the HFD group. The extract at 300 mg/kg showed intermediate effects (9.89 ± 2.77 mmol/L). No statistically significant differences were observed in liver or spleen weights among the groups. In summary, the mangosteen pericarp ethanol extract is rich in phenolics, exhibits moderate antioxidant activity in vitro, and demonstrates dose-dependent protective effects against HFD-induced hyperglycemia. While the in vivo metabolic assessment was limited to selected endpoints, these findings provide preliminary evidence supporting the potential of the mangosteen pericarp extract for further investigation in diet-induced metabolic dysfunction models.